Tiny beautiful things ebook Advice from dear sugar. - Strayed, Cheryl (2012)
NOW A HULU ORIGINAL SERIES • NEW YORK TIMES BESTSELLER • REESE'S BOOK CLUB PICK • An anniversary edition of the bestselling collection of "Dear Sugar" advice columns written by the author of #1 bestseller Wild —featuring a new preface and six additional columns. For more than a decade, thousands of people have sought advice from Dear Sugar—the pseudonym of bestselling author Cheryl Strayed—first through her online column at The Rumpus, later through her hit podcast, Dear Sugars , and now through her popular Substack newsletter. Tiny Beautiful Things collects the best of Dear Sugar in one volume, bringing her wisdom to many more readers. This tenth-anniversary edition features six new columns and a new preface by Strayed. Rich with humor, insight, compassion—and absolute honesty—this book is a balm for everything life throws our way.